2017
DOI: 10.4236/aim.2017.77044
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fermentation on the Proximate Composition of Irish (<i>Solanum tuberosum</i>) and Sweet Potato (<i>Ipomoea batatas</i>) Peels

Abstract: Fermentation has been exploited to improve agricultural waste products.Fermentation of Sweet potato (Ipomoea batatas) and Irish potato (Solanum tuberosum) peels was carried out by soaking in clean water for 96 hours at room temperature during which samples were collected daily for microbial, physicochemical and proximate analysis. Microbial load of both peels ranged from 9.0 × 10 5 to 8.6 × 10 6 cfu/ml; 1.5 × 10 6 to 7.4 × 10 6 sfu/ml and 1.2 × 10 6 to 2.0 × 10 6 sfu/ml for bacteria, fungi and yeast respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The quantity of carbohydrate which is mainly starch was in accordance with the value reported by Badr SA and El-Wasif 43 . Another research report by Adegunloye and Oparinde 2017 44 has recorded the carbohydrate content of 72.60% in potato peels while determining the effects of fermentation on the proximate composition of Irish ( Solanum tuberosum ) peels.…”
Section: Resultsmentioning
confidence: 99%
“…The quantity of carbohydrate which is mainly starch was in accordance with the value reported by Badr SA and El-Wasif 43 . Another research report by Adegunloye and Oparinde 2017 44 has recorded the carbohydrate content of 72.60% in potato peels while determining the effects of fermentation on the proximate composition of Irish ( Solanum tuberosum ) peels.…”
Section: Resultsmentioning
confidence: 99%
“…The SP protein has been linked with health benefits, including antioxidant activity, decreased levels of triglyceride in the blood, and anticancer and antiproliferative effects [ 50 , 51 , 52 , 53 ]. Furthermore, previous reports have indicated that the fat content in potato peels are two times higher than it is in peeled potatos [ 54 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The fermentation process usually decreases the soluble dietary fiber more than the insoluble dietary fiber content and this makes total crude fiber content of the fermented products to decrease (Brennan et al., 2013 ; Bunzel et al., 2001 ; Comino et al., 2018 ). The decrease in fiber contents after fermentation is an indication of softening of fibrous tissues and increased digestibility due to activities of microorganisms which are known for the bioconversion of carbohydrates and lignocellulose into protein (Adegunloye & Oparinde, 2017 ; Igbabul et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%